ANALYTIC HIERARCHY PROCESS (AHP) UNTUK PENENTUAN RANGKING PENGGUNAAN LAHAN - Anita Theresia Kurniawati; Misbahul Munir (2477 - 6165, 2017)
In urban spatial planning, the Local Government prioritizes land use to support planning development. The use of available land in an area must be adjusted to the function. So far, sometimes in an area the use of available land in an area does not fit with its function. Therefore, in this research will be determined the priority and ranking of land use by using Analytic Hierarchy Process (AHP). Ranking is based on four aspect criterias: social demography, economic, spatial and regional plan (RTRW), and environmental aspect. Based on the alternatives and criteria and also subcriteria, the decision hierarchy model is made. Then it will be assessed for the comparison between criterias and subcriterias and their consistency value. The result is achieved by using Expert Choice software version 11 and analysis, it showed that the main priority of land allocation in Sidoarjo regency was used as agricultural land (31.9%).